2020
DOI: 10.1109/ojies.2020.3001406
|View full text |Cite
|
Sign up to set email alerts
|

Passivity-Based Analysis and Design of Linear Voltage Controllers For Voltage-Source Converters

Abstract: This paper presents a systematic evaluation on the impedance passivity of voltage-controlled voltage-source converters. The commonly used single-and dual-loop control structures with different linear controllers are compared extensively, considering the effect of the time delay involved in the control loop. A virtual impedance control, co-designed with different voltage control schemes, is then proposed to eliminate the negative output resistance till half of the sampling frequency, which improves the system s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 62 publications
1
70
0
Order By: Relevance
“…Fig. 2 shows the derived small-signal model of the dualloop voltage-controlled VSC [37]. Z ol , G uv , G ii , and G ui are the open-loop transfer functions of the plant, which are…”
Section: A Voltage Control Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2 shows the derived small-signal model of the dualloop voltage-controlled VSC [37]. Z ol , G uv , G ii , and G ui are the open-loop transfer functions of the plant, which are…”
Section: A Voltage Control Modelingmentioning
confidence: 99%
“…10 Bode diagrams of VC loop gains and VC output impedances the low-frequency (much lower than f1) impedance is mainly shaped by the current controller gain, which is usually designed as large as possible, since the current controller gain is aimed to provide active damping for the LC resonance [38]. In the high-frequency range (much higher than f 1 ), it can be found that the impedance is mainly shaped by the LC resonance including the time-delay effects [37]. Consequently, the limited VC bandwidth results in a non-negligible Zo around f 1 , which can interact with the power control impedances and further affect the VSC output impedance.…”
Section: ) Voltage Control Impactmentioning
confidence: 99%
“…This is demonstrated by means of the experimental results for the two examined cases reported in Fig. 8 (b) and (c) [38], [39], where single-phase converter currents before and after the capacitor filter are shown, indicated respectively with i 1a and i 2a , along with the capacitor voltage v a , and the grid voltage v ga .…”
Section: • Voltage Vector Controlmentioning
confidence: 74%
“…is used to eliminate the capacitor voltage error u f,ref − u f and the transfer function H u (z) from the load current i o can be used to include disturbance feedforward for the voltage controller, e.g., as in [14], [16], [28], to improve disturbance rejection properties of the controller. The MISO transfer function C u (z) can be used to add active damping.…”
Section: A Voltage Controllermentioning
confidence: 99%
“…As a result, several different control methods have been proposed with distinct properties. Considering linear controllers, the majority of the voltage control algorithms can be roughly divided into single-loop [9]- [14] and cascade [3]- [5], [8], [15], [16] control algorithms. Non-linear methods based on, e.g., model-predictive Manuscript received October 6, 2020; revised January 19, 2021; accepted February 21, 2021.…”
Section: Introductionmentioning
confidence: 99%